Thai government concerns towards Thai students in Saudi Arabia and Egypt (1940s-1960s) - Hayimasae, Numan (2013)
Thai government initiated to concern towards Thai students in Saudi Arabia in the 1940s and in Egypt in the 1050s respectively.The intensive concern to Thai students could be carried out well after the Thai consulate in Jeddah was set up in the 1950s.At least three approaches had been used to discover namely, to appoint officials to take care of their works and activities, to cooperate with students' guardians to report any details of their son and daughters and to associate with Saudi Arabia and Egypt government in monitoring Thai students.The major aim to concern with was to ensure they did not involve into political movement and other matters that cause deterioration to the Thai government. Graduates from they were considered to be important graduates after returning homeland.